Assessing animal species at risk for SARS-CoV-2 transmission: Bioinformatic analysis based on Angiotensin-Converting-Enzyme (ACE2) homology in edible and other animals - Recalde-Soliz, Veronica Lissette; Idrovo-Espin , Fabio Marcelo (Acta Agraria Debreceniensis, 2025)
A novel coronavirus called SARS-CoV-2 was detected in December 2019, leading to the COVID-19 pandemic that began in Wuhan, China. This virus is classified as severe acute respiratory syndrome SARS-CoV-2 due to its significant similarities with the SARS-CoV virus. Initially, bats were recognized as the primary animal hosts, but later research indicated that other animals could also serve as reservoirs, posing health risks, particularly for those species consumed by humans. SARS-CoV-2 binds to the angiotensin-converting enzyme 2 (ACE2) as its cellular receptor, utilizing the receptor-binding domain (RBD) of its spike protein, much like SARS-CoV does. The study aimed to identify animals, particularly edible animals, that may be susceptible to infection by SARS-CoV-2. This was achieved through bioinformatics techniques, including alignment analysis of genomic sequences from selected animals, identity percentages comparison, and phylogenetic analysis based on the interaction between ACE2 and the receptor-binding domain (RBD) of SARS-CoV-2. This analysis identified rabbits, donkeys, alpacas, horses, wild boars, field rats, and monkeys as potentially susceptible edible animals. Additionally, primates were highlighted due to their close genetic resemblance to humans. Overall, 22 animals worldwide were identified as susceptible, marking them as possible reservoirs and hosts for the virus, emphasizing the need for vigilance around animals that humans may contact or consume.